Contributions of health technologies in risk assessment for suicide behavior: an integrative review - Daniel de Macêdo Rocha; Andreia Karla de Carvalho Barbosa Cavalcante; Aline Costa de Oliveira; Claudia Daniella Avelino Vasconcelos Benício; Ana Maria Ribeiro dos Santos; Lídya Tolstenko Nogueira (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to identify how health technologies contribute to risk assessment for suicidal behavior. Methods: an integrative review carried out on the MEDLINE, CINAHL, Web of Science, SCOPUS, LILACS and BDENF databases. The sample consisted of 12 primary studies, with no temporal or language delimitation. Analysis of results occurred descriptively. Results: the technologies included assistance and teaching aspects favorable to data screening, monitoring and navigation, capable of predicting individual, biological, clinical, psychological, environmental and social markers for suicidal behavior. Thus, measurement scale, software and computational algorithms constituted valid and sensitive instruments for improving performance, expanding skills and knowledge, good care practices, effective communication and assistance planning. Conclusion: the identified technologies proved to be effective in identifying risk states for suicidal behavior, representing effective resources for directing care and necessary interventions.